Lack of gender-specific antibody recognition of products from domains of a var gene implicated in pregnancy-associated plasmodium falciparum malaria. - Jensen, A. T. R.; Zornig, H. D.; Buhmann, C.; Salanti, A.; Koram, K. A.; Riley, E. M.; Theander, T.G.; Hviid, L.; Staalsoe, T. (My University, 2003)
Gender-specific and parity-dependent acquired antibody recognition is characteristic of variant surface antigens (VSA) expressed by chondroitin sulfate A (CSA)-adherent Plasmodium falciparum involved in pregnancy-associated malaria (PAM). However, antibody recognition of recombinant products of a specific VSA gene (2O2var1) implicated in PAM and transcribed by a CSA-adhering parasite line did not have these characteristics. Furthermore, we could not demonstrate preferential transcription of 2O2var1 in the CSA-adhering line versus the unselected, parental isolate. Our data call for circumspection regarding the molecular identity of the parasite ligand mediating adhesion to CSA in PAM.
Keywords: EMTREE drug terms: chondroitin sulfate; gene product; membrane antigen EMTREE medical terms: animal cell; animal experiment; animal model; animal tissue; antibody specificity; antigen expression; antigen recognition; article; controlled study; female; gender; gene expression regulation; gene identification; gene isolation; genetic recombination; genetic selection; human; human cell; human tissue; ligand binding; malaria falciparum; male; molecular biology; mouse; nonhuman; parity; Plasmodium falciparum; pregnancy associated malaria; pregnancy complication; priority journal; protein domain; sex difference; transcription regulation; vsa gene